Eficácia da reabilitação neuropsicológica no transtorno afetivo bipolar: um estudo controlado - Fabricia Quintao Loschiavo - Alvares (2013)
Background: Cognitive deficits are commonly found in patients with bipolar disorder (BD), not only in mania and depression phases, but even during the remission of symptoms, called euthymia. Among the affected cognitive domains, it is highlighted memory, attention and executive functions which are intrinsically related to functionality. Recent investigations have corroborated the fact that for the best therapeutic management of BD, the treatment should include interventions focused on cognition, more precisely, the neuropsychological rehabilitation (NR). This consists in proposing efforts to improve the functionality and quality of life of people with cognitive impairments, through strategies aimed to reducing the impact of cognitive impairment in the occupations of the individual through the use of specific technical training and compensation, which could contribute to a better functional outcome. Objective: This study aimed to evaluate the overall effectiveness of a NR protocol, directed to the treatment of memory, attention and executive functions in patients with BD. In order to achieve this, specific objectives were outlined, namely: cultural adaptation and investigation of psychometric properties of the DEX -R , a functional assessment of executive function , memory and attention , which was used as am efficacy measure; verify the impact of the proposed NR protocol in executive functions , memory and attention , quality of life and coping, both ate the post-intervention and at follow -up (six months after the suspension of the protocol ) and investigate the number of episodes of mood swings , hypomania , mania and / or depression on the six months following the conclusion of NR protocol. Methods: concerning DEX R studies, these comprised a sample of healthy subjects control group (n = 300) (recruited from a convenience sample), as well as a group of patients diagnosed with BD. An exploratory factor analysis followed by an intergroup comparison to investigate the psychometric properties using Rasch analysis was performed. For research on the analysis of the effectiveness of NR , patients with BD eligible for the study were allocated pseudo - randomly into two groups : control group ( CG) n = 30 , consisting of patients treated only by pharmacotherapy and Rehabilitation group ( NRG ) , n = 20 , comprising patients who received pharmacotherapy and NR protocol . The protocol established after conducting a pilot study consisted of 14 weekly individual sessions, divided into three modules: Psychoeducation and Humor Monitoring Strategies, Rehabilitation of Executive Functions, Rehabilitation and Memory Care. All sessions were structured with standardized techniques for each cognitive domain approach. EMEP (coping) , Disexecutive Questionnaire Revised - DEX -R ( executive functions, memory and attention) and WHOQOL -BREF ( quality of life) were used as effectiveness measures. Mixed design ANOVA for repeated measures was conducted to compare the treatment effect in the groups scores (pre , post andfollow -up ) . All analyzes were performed using SPSS 20.0 - Windows and / or RUMM 2030. For all analyzes, the level of significance was set at p <0.05. Results: DEX -R was sensitive for the assessment of executive functions, memory and attention in the Brazilian context, and therefore was adopted as a measure of efficacy for evaluation of protocol NR . The items were grouped into three factors: social regulation and self -regulation (related to orbito -frontal circuit functions) , motivation and attention ( related to its previous cingulate circuit functions ) and flexibility , fluency and working memory ( dorsolateral circuit -related functions ) . Regarding the effectiveness of NR, for all intergroup comparisons ( pre , post and follow -up ) a significant difference was found on NRG scores ( p < 0.05). No statistical differences were observed in the GC. The effect size of the differences between pre - and post-test were higher for the group under treatment ( d > 0.8 ) for all efficacy measures. Conclusion: patients from NRG exhibited significant improvement in all domains assessed, as well as a significant increase in functional abilities, i.e., gains in quality of life, coping skills focused on problem and improvements in executive function , attention and memory. The results corroborate previous findings that indicate that patients with BD may benefit from the NR as an important therapeutic tool to promote a better functional performance. The findings arising from this PhD work were discussed based on psychometric and neuropsychological aspects, organized into specific articles. Finally, hypotheses about methodological limitations of the studies and proposals for improvement in future research were presented.